APPLICATION OF ERYTHROPOIETIN THETA IN THERAPY OF ANEMIA IN ONCOLOGIC PATIENTS - O. A. GLADKOV (Медицинский совет, 2016)
Anemia is one of the most frequent complications arising in patients with malignant growths, it is characterized by reduction of hemoglobin level and disturbance of a number of physiological and metabolic processes in the organism, impairing the course of the disease and patients’ life quality. The major reasons of the hemoglobin concentration reduction include: anemia induction by the tumour, chemotherapy and chronic inflammation anemia. The most frequent methods of therapy are: red blood cell transfusion, prescription of erythropoiesis-stimulating drugs (ESA) and iron supplements. Erythropoietins indication is the most preferential method taking into account complications related to red blood cell transfusions. Erythropoetins alpha and beta are the most well-known and well-studied among the first generation ESAs. The erythropoietin theta is not a biological analogue. It is represented as a separate product. It demonstrated non-inferiority of anemia treatment in cancer patients as compared to the erythropoietin beta in studies. Dosage of 20 000 IU of erythropoietin theta was sufficient for the full hemoglobin response in more than a half of patients.